5G-Enabled Distributed Systems: Enabling Next-Generation Applications through Ultra-Low Latency Networks - Venkateswarlu Poka (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article explores the transformative potential of 5G networks in enabling advanced distributed systems across multiple domains. By combining ultra-low latency, high bandwidth, and massive connection density capabilities, 5G technology overcomes traditional network limitations that have constrained distributed computing applications. The article examines three high-impact application areas where 5G capabilities are particularly beneficial: augmented and virtual reality (AR/VR), autonomous vehicle communication systems, and smart manufacturing environments. Through article architectural frameworks, performance metrics, and real-world implementations, the article demonstrates how 5G networks fundamentally alter system design approaches while addressing security, reliability, and resource optimization challenges. The article reveals that 5G-enabled distributed systems represent not merely an incremental improvement but a paradigm shift that enables new categories of applications previously infeasible with earlier network technologies.